2022
DOI: 10.1007/s12652-021-03658-z
|View full text |Cite
|
Sign up to set email alerts
|

A survey on extremism analysis using natural language processing: definitions, literature review, trends and challenges

Abstract: Extremism has grown as a global problem for society in recent years, especially after the apparition of movements such as jihadism. This and other extremist groups have taken advantage of different approaches, such as the use of Social Media, to spread their ideology, promote their acts and recruit followers. The extremist discourse, therefore, is reflected on the language used by these groups. Natural language processing (NLP) provides a way of detecting this type of content, and several authors make use of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 144 publications
0
8
0
Order By: Relevance
“…A corpus can consist of texts in multiple languages, known as a multilingual corpus, or texts in just one language, known as a monolingual corpus. Within extremism identi cation, the scarcity of data is a signi cant obstacle (Torregrosa et al 2022), as only a limited number of datasets are accessible on the internet. Our research involves the creation of three multilingual corpora, two of which focus on extremism and the remaining one on radicalization.…”
Section: Corpus Buildingmentioning
confidence: 99%
“…A corpus can consist of texts in multiple languages, known as a multilingual corpus, or texts in just one language, known as a monolingual corpus. Within extremism identi cation, the scarcity of data is a signi cant obstacle (Torregrosa et al 2022), as only a limited number of datasets are accessible on the internet. Our research involves the creation of three multilingual corpora, two of which focus on extremism and the remaining one on radicalization.…”
Section: Corpus Buildingmentioning
confidence: 99%
“…Jihad can intercede for the bereaved family F. Gunawan, S. Kuraedah, A. M. Amir, M. F. Ubaidillah & S. Boulahnane, Transitivity and critical discourse analysis on a testament: A woman's involvement in jihad | 530 and send them to heaven. Torregrosa et al (2022) reported that war against the Thagut government is an integral part of the Salafi jihadist's narrative construction. They use a negative tone, specific slang, and idioms demonstrating their unique language style such as 'playing football' which refers to war against government security staff.…”
Section: Concept Of Struggle In the Context Of Religious Warmentioning
confidence: 99%
“…Petri nets [49] A Petri net is a mathematical language tool used for analyzing concurrent processes that occur in multicomponent systems (distributed systems). Natural Language Processing (NLP) [50] NLP employs a collection of computational techniques for making human languages accessible to computers, particularly with the goal of enabling computers to interpret and generate human language. Multi-objective Optimization [51] A multi-objective optimization problem is a problem dealing with more than one objective function.…”
Section: Reference Definitionmentioning
confidence: 99%